Thermoregulation of Eremias argus alters temperature-dependent toxicity of beta-cyfluthrin: Ecotoxicological effects considering ectotherm behavior traits. (15th January 2022) - Wang, Zikang; Liu, Ran; Zhang, Luyao; Yu, Simin; Nie, Yufan; Deng, Yue; Liu, Rui; Zhu, Wentao; Zhou, Zhiqiang; Diao, Jinling
Abstract: Risk assessments of the ecotoxicological effects insecticides impose on ectotherms have increasingly considered temperature. However, the changes toxicants induce in thermoregulatory behavioral traits may lead to a divergence of thermal selection and temperature-dependent changes of contaminant toxicity. This study demonstrated the interaction of behavioral thermoregulation and temperature-dependent toxicity of beta-cyfluthrin (BC) in the lizard Eremias argus . Based on the negative relationship between temperature and BC toxicity, seeking a warming environment was assumed to represent a self-rescue behavior (and vice versa). The results showed that BC-treated lizards (0–20 μg/g body weight (bw)) showed such self-rescue behavior, while lizards exposed to an extremely high BC dose (200 μg/g bw) sought a cooler environment. Biochemical assays showed that BC affected neurotransmitter systems, caused oxidative stress, and interfered with ion-transport in the central nervous system. Biomarkers of the cholinergic and glutamatergic system, ion-transport function, and oxidative stress were identified as potential biochemical variables related to thermoregulatory behavior. Apparently, seeking a warmer environment is a survival strategy with the aim to neutralize BC toxicity, while seeking a cooler environment aims to attenuate the harmful effects of metabolic and oxidative stress, and to decelerate internal BC diffusion. This phenomenon could be also explained by the concept of the "cooling trap", i.e., a behavior where cooler temperatures are sought. This impairs survival after exposure to BC at it has a negative temperature coefficient, derived from a dysfunction of the central nervous system regarding thermoregulation caused by the high dosage of neurotoxicant and resulting temperature maladaptation. Implications of the interaction between thermoregulatory behavior and temperature-dependent toxicity are presented, which may aid further temperature-dependent risk assessments. Graphical abstract: Image 1 Highlights: Beta-cyfluthrin (BC) has negative temperature-dependent toxicity (TDT) in lizards. BC caused oxidative stress and neural disorder in the central nervous system. BC influenced thermoregulatory strategies, which varied with different doses. Behavior to seek cooler places impaired survival and may indicate a "cooling trap". Relations between thermoregulation and TDT impede risk assessments in ectotherms.